EVALUASI SISTEM PENGELOLAAN OBAT INSTALASI PERBEKALAN FARMASI DINAS KESEHATAN KOTA SEMARANG TAHUN 2007 - mohammad djatmiko; aqnes tuning dyah a; maulita cut nuria (Universitas Wahid Hasyim Semarang, 2009)
ABSTRACTDrug management is an activity covering planning, provision, storing, distributing, administering andrecording or reporting on the drug used. The purpose of this research was to evaluate the management of the drugsin Departement of Pharmacy Inventories (DPI) of Semarang Health Office (SHO).This research was non-experimetal in nature in which the needed data were collected retrospectively. Thecollected data were in the forms of records on the drugs plans, Records on the Use dan Requests of Drugs (RURD)and results of interviews to the DPI head. The evaluation on the drug management used eleven indicators providedby the fixed procedures for drug management in central java province. The data were converted into percentages andrupiah values, which were then analyzed descriptively.The analyses showed that the drug management by DPI during the period of 2007 had produced effectiveresults as indicated by an effectiveness level of 97,59% for the drug provision, a accuracy level of 98,19% for drugplanning, an effectiveness level of 89,76% for safe provision of the drugs, a conformity level of 100% for the drugitems to the DOEN, a percentage of 0% for average drug supply, a percentage of 2,46% for the times during whichthere was a status of empty for the drug, an abuse level of 8,35% for the miss-distribution of the drugs, a percentageof 3,15% for non-prescription drugs, a percentage of 1,57% for expired drugs with a financial value of Rp.10.094.590 and a percentage of 3,94% for broken drugs with a financial cost of Rp. 43 2.537and a accuracy level of46,62% for delivery t imes for RURD.Keywords : evaluation, drug management, DPI Semarang